Augmented Reality App in Pre-School Education: Children’s Knowledge About Animals - Yılmaz, Zeynel Abidin; Can Gözüm, Ali İbrahim (Southeast Asia Early Childhood Journal, 2023)
This study aims to determine the learning outcomes of children in educational settings by using an AR (Augmented Reality) app for animals in classroom activities. To achieve this, the study used sequential exploratory research design, applied in both quantitative and qualitative research. The participants in the study are 2 teachers and 37 children working in the kindergarten affiliated to the Ministry of National Education in the central district of Kilis Province in the 2019-2020 academic year. The augmented reality app was used in one group (n=18) of children, and not in the other group (n=19). The children were given an animal recognition test prepared by the researchers before the app was used and again afterward in an attempt to discover how the AR app affected learning. The study determined that while animal recognition increased in both the AR and non-AR groups, the children in the group where the AR app was used recognized more animals than the other group. As a result of the analyses made of the animal pictures drawn by the children who used the AR app, it was understood that the children had the opportunity to discover details about the animals. Additionally, the study conducted analyses of animal pictures drawn by the children who used the AR app, revealing that the app provided children with opportunities to discover and explore intricate details about the animals.